Pre-Operative Evaluation of Petrous Temporal Bone Pathologies by CT and MRI in Cochlear Implant Candidates - Muhammad Akhtar, Shoaib Nasir, Nida Shoaib, Khalid Masood, Muhammad Mubeenul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate pathologies of the petrous temporal bone in cochlear implant candidates on CT and MRI preoperatively. Methods: A cross-sectional study was conducted at Combined Military Hospital Lahore from Jan 2014 to April 2016. 163 candidates were evaluated on CT and 149 were evaluated on MRI. All patients belonged to pediatric age group. Pathologies were grouped using classification of Sennaroglu & Saatci and every pathology was sought in all the cases ensuring that the pathologiesare not missed. Results: High-resolution CT scan temporal bone revealed 69.9% normal studies. Chronic otitis media with mastoiditis was major abnormality observed in 16.6% of cases. Unilateral mastoiditis was seen in 6.1% of patients. Bilateral CSOM without mastoiditis was seen bilaterally in 1.8% of cases. While unilateral CSOM was observed 0.6 % of patients. Among inner ear malformations, Mondini malformation was seen in 4 cases (2.5%). A high jugular bulb was seen in 2 cases (1.2%).93.3% of cases were labeled as normal study on MRI. Four cases showed Mondini malformation. Infective process of middle ear showed a cumulative frequency of 2.7%. Inner ear aplasia was found in one patient. Sclerosing labyrinthitis was also found in one case. Conclusion: Both CT and MRI have substantial role in pre-operative evaluation of petrous temporal bone in cochlear implant candidates. Preoperative evaluation of petrous temporal bone by CT scan and MRI successfully identifies pathologies which can be absolute or relative contraindications of the cochlear implant as well as conditions in which surgical procedure needs to be modified. Keywords: Cochlear implants, HRCT temporal bone, MRI cochlea, Mastoiditis, Mondini malformation